Design, User Experience, and Usability: User Experience Design for Diverse Interaction Platforms and Environments Third International Conference, DUXU 2014, Held as Part of HCI International 2014, Heraklion, Crete, Greece, June 22-27, 2014, Proceedings, Part II - Marcus, Aaron; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The four-volume set LNCS 8517, 8518, 8519 and 8520 constitutes the proceedings of the Third International Conference on Design, User Experience, and Usability, DUXU 2014, held as part of the 16th International Conference on Human-Computer Interaction, HCII 2014, held in Heraklion, Crete, Greece in June 2014, jointly with 13 other thematically similar conferences. The total of 1476 papers and 220 posters presented at the HCII 2014 conferences were carefully reviewed and selected from 4766 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of Human-Computer Interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The total of 256 contributions included in the DUXU proceedings were carefully reviewed and selected for inclusion in this four-volume set. The 76 papers included in this volume are organized in topical sections on design for the web, design for the mobile experience, design of visual information, design for novel interaction techniques and realities, games and gamification.
Design for the web -- Design for the mobile experience -- Design of visual information -- Design for novel interaction techniques and realities -- Games and gamification.
Keywords: User interfaces (Computer systems).; Computers and civilization; Application software; Information storage and retrieval; User Interfaces and Human Computer Interaction; Computers and Society; Information Systems Applications (incl. Internet).; Information Storage and Retrieval